A Thin and Efficient Invisibility Cloak Designed by Using Genetic Algorithm from Layers of Ordinary Dielectric Materials - Xiaohui Wang; Elena Semouchkina (Fundamental Research and Application of Physical Science Vol. 9, 2023)
The objective of this work is to develop a thin and efficient transmission cloak for hiding objects larger than the wavelengths of incident radiation by using multi-layer coating composed of ordinary dielectrics, instead of meta- and plasmonic materials. The genetic algorithm-based optimization process is used to determine the parameters of the cloak layers, and the fitness function is the reciprocal of the total scattering cross-width of the cloaked target, which is obtained from the solution of the Helmholtz equation. The proposed cloak demonstrates better cloaking efficiency than does a similarly sized metamaterial cloak designed by using the transformation optics relations.